Can magnetic nanoparticles enhance adoptive cell therapy via driving migration of lymphocytes into tumors? - Irina Chikileva; Polina Fedorova; Irina Shubina; Stanislav Pshenichnikov; Kateryna Levada; Vyacheslav Abramov; Mikhail Kiselevskiy (Open Exploration Publishing Inc., 2024)
Therapy of malignant tumors still represents a huge problem for healthcare, since these diseases lead to a high rate of disability and premature death of the population. The main problems of adoptive cell therapy for malignant tumors are a low rate of migration of effector lymphocytes into tumors, as well as their low activity in tumors due to suppressive tumor microenvironment. In addition, it should be noted that systemic intravenous administration of a large number of activated lymphocytes may be accompanied by a pronounced cytokine release syndrome, which leads to significant negative side effects, including high temperature, blood clotting disorders, aggression of immune cells against their own tissues, even neurotoxicity. Functional nanomaterials, such as magnetic nanoparticles with various surface modifications (PEG, PEI, DMSA, citrate, etc.) are highly promising agents for targeted delivery of different anti-tumor substances. Magnet-driven enrichment of effector anti-tumor lymphocytes in tumors would highly increase the effectiveness and enhance safety of adoptive lymphocyte therapy. However, different research groups obtained opposing data about the feasibility and efficiency of such approach. Thus, this review is focused on experimental details of the contradicting studies and aims to elucidate the possible reasons of these controversies and the best practices to efficiently target lymphocytes into tumors.